2021
DOI: 10.30918/aerj.91.20.222
|View full text |Cite
|
Sign up to set email alerts
|

Exercise addiction of individuals receiving sports services and analysis of social appearance anxiety levels

Abstract: The purpose of this study was to examine exercise addiction and social appearance anxiety levels of students studying at the faculty of sports sciences in terms of various variables. There were 170 participants in the study. “Personal Information Form”, “Exercise Addiction Scale” and “Social Appearance Anxiety Scale” were applied to the participants. Whether the data provided the assumption of normality was evaluated by the skewness and kurtosis test. It was decided that the values obtained as a result of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…It can be said that a person's healthy lifestyle skills affect their perception of social appearance, and physical activity also plays an important role in the formation of this perception 7 . Therefore, it can be said that because individuals who participate in exercise programs make it a habit to play sports in order to maintain their health in everyday life, the physical and mental benefits that individuals receive from sports activities make them more at peace with themselves 8 . Regular and moderate exercise neutralizes stress hormones and activates the hormone endorphin, known as the happiness hormone, which contributes to making a person feel happier and more energetic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be said that a person's healthy lifestyle skills affect their perception of social appearance, and physical activity also plays an important role in the formation of this perception 7 . Therefore, it can be said that because individuals who participate in exercise programs make it a habit to play sports in order to maintain their health in everyday life, the physical and mental benefits that individuals receive from sports activities make them more at peace with themselves 8 . Regular and moderate exercise neutralizes stress hormones and activates the hormone endorphin, known as the happiness hormone, which contributes to making a person feel happier and more energetic.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature on body image, it is focused on testing how physical activity and sport are associated with more positive body image, or how sports and physical activity interventions can be used to improve body image 17 . When we look at the literature, there are many studies that deal with social appearance anxiety 26,27,28,29,8,30 and psychological well-being 31,32,33,34,35,36,37,38,39 with different variables in the context of sports. However, no study has been found in which the relationship between social appearance anxiety and psychological well-being is discussed together in the context of pilates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies concluding that social appearance-related anxiety levels will be at lower levels also draws attention in athletes who do fitness and regularly receive sports services with a high level of socialization and self-esteem (Erkmen and Aşçı, 2016;Korkmaz and Uslu, 2020;Duyan and Günel, 2021). Schneider, and Schupp (2014), in a study they conducted on social comparison and life satisfaction, emphasized that there are individual differences arising from the psychology of the person.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is beneficial and valuable to the promotion of physical fitness and health [2]. Sports activities made their exercise a habit to protect their health in daily life [3]. Exercise and life satisfaction levels increase the academic achievement of students [4].…”
Section: Introductionmentioning
confidence: 99%